Public support intensity and company R&D performance: Evidence from a dose-response model - Giovanni Cerulli; Bianca Potì (European Regional Science Association (ERSA), 2014)
This paper presents an original econometric model for estimating a dose-response function through a regression approach when: (i) treatment is continuous, (ii) individuals may react heterogeneously to observable confounders, and (iii) selection-into-treatment may be potentially endogenous. After describing the model, two estimation procedures are suggested: one based on OLS under Conditional Mean Independence (or CMI), and one based on Instrumental-Variables (IV) under selection endogeneity. The paper goes on by presenting ctreatreg, a user-written Stata routine for an easy implementation of such a model, thereby performing a Monte Carlo experiment to test the reliability of the model and of its software implementation. Finally, an application to real data for assessing the effect of public R&D support on companies' R&D expenditure is presented and results briefly commented. The usefulness of such a model for program evaluation is clearly stressed.
Keywords: C21; C87; D04; 330; treatment effects; dose-response function; continuous treatment; Monte Carlo; R&D support